Kinetics for describing the creaming of protein-stabilized O/W emulsions by multiple light scattering - Panizzolo, Lius Alberto (2014)
In the present work, new kinetics to describe the creaming stability of oil-in-water emulsions determined by backscattering measurements (BS) is proposed. The emulsions assayed exhibited a different backscattering profiles regarding creaming destabilization, hyperbolic and sigmoid one. Hyperbolic behavior can be described by a second order kinetics, where kh could be equaled to a rate constant that describes the creaming process and its values would indicate the stability of emulsions. While for the sigmoid BS pattern, kinetics with two terms, is adequate to describe the creaming process in contrast to kinetics previously reported in the literature. The kh value has the same meaning as before, and ks indicates the delaying effect on the creaming rate.